Hierarchical MoSe2 Nanosheets/Reduced Graphene Oxide Composites as Anodes for Lithium‐Ion and Sodium‐Ion Batteries with Enhanced Electrochemical Performance. Issue 6 (13th August 2015) - Zhang, Zhian; Fu, Yun; Yang, Xing; Qu, Yaohui; Zhang, Zhiyong
Abstract: The preparation and electrochemical storage behavior of hierarchical MoSe2 /reduced graphene oxide (rGO) composites were studied. The preparation was achieved by a facile hydrothermal route. The results show that MoSe2 has a high capacity for lithium ion and sodium ion storage and that the incorporation of rGO has further improved the electrochemical property of MoSe2 effectively. As anode materials for lithium‐ion and sodium‐ion batteries, the MoSe2 /rGO composites demonstrate excellent rate performance and cycling stability of 917 mA h g −1 after 100 cycles for Li + storage and 430 mA h g −1 after 200 cycles for Na + storage at a current density of 0.5 A g −1, which is attributed to the robust hierarchical structure and the synergistic effects between MoSe2 nanosheets and rGO. Therefore, the electrochemical evaluations suggest that the obtained hierarchical structure MoSe2 /rGO composites hold great potential as anode materials for lithium‐ion and sodium‐ion batteries. Abstract : Hierarchical MoSe2 /rGO composites in which MoSe2 nanosheets are anchored on the surface of reduced graphene oxide (rGO) nanosheets were prepared through a facile strategy. As anode materials for lithium‐ion and sodium‐ion batteries, the MoSe2 /rGO composites demonstrate excellent rate performance and cycling stability, which are attributed to the robust hierarchical structure and the synergistic effects between MoSe2 and rGO.